Pemetaan Udara Dengan Pesawat Tanpa Awak Untuk Survey Cepat Karhutla Di Provinsi Kalimantan Tengah: Aerial Mapping with Unmanned Aircraft for Rapid Survey of Forest and Land Fires in Central Kalimantan Province - Petrisly Perkasa; Yusuf Aguswan; Samuel Layang; Prasatya Aji Santoso; Glen Wildodo (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
The capital city of Central Kalimantan, namely Palangka Raya City, almost every year there are always forest and land fires that harm many people both economically, socially and environmentally which will certainly hinder the development of this city, Palangka Raya has a fire-prone area of 33,824 ha. Monitoring forest and land fires with manual field visits which can be very time consuming. To shorten the time and expand the ability to monitor forest and land fires, the use of Unmanned Aerial Vehicles (UAV) or drone images is one solution to map fire-prone areas in all fields. The aerial photography produced by the UAV is processed using the photogrammetric method to produce a responsible aerial photo map covering an area of 41.92 with 17 benchmark points to block fires in the UPR campus forest from spreading.